The Relationship of Cloud Number and Size With Their Large‐Scale Environment in Deep Tropical Convection. Issue 15 (5th August 2019) - Louf, Valentin; Jakob, Christian; Protat, Alain; Bergemann, Martin; Narsey, Sugata
Abstract: Accurately representing the properties and impact of tropical convection in climate models requires an understanding of the relationships between the state of a convective cloud ensemble and the environment it is embedded in. We investigate this relationship using 13 years of radar observations in the tropics. Specifically, we focus on convective cell number and size and quantify their relationship to atmospheric stability, midtropospheric vertical motion and humidity. We find several key convective states embedded in their own unique environments. The most area‐averaged rainfall occurs with a moderate number of moderate size convective cell in an environment of high humidity, strong vertical ascent, and moderate convective available potential energy (CAPE) and convective inhibition (CIN). The strongest rainfall intensities are found with few large cells. Those exist in a dry and subsiding environment with both high CAPE and CIN. Large numbers of convective cells are associated with small CAPE and CIN, weak ascent, and a moist midtroposphere. Key Points: The relationship between a convective cloud ensemble and its environment is studied to improve the representation of tropical convection in models The strongest rainfall intensities are found with few large cells those exist in a dry and subsiding environment with both high CAPE and CIN The convective cell number and size are quantified and their relationship to atmospheric stability, vertical motion, and humidity is studied